2018
DOI: 10.1177/2325967118771845
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in the Orthopaedic Sports Medicine Fellowship Match, 2010-2017

Abstract: Background:Sports medicine is one of the most competitive fellowships in orthopaedic surgery. Despite its popularity, fellowship applicants have limited understanding of the orthopaedic sports medicine fellowship match process.Purpose:To define key outcomes in the orthopaedic sports medicine fellowship match, including the overall match rate, number of programs filled, and number of applicants ranked by programs that filled between 2010 and 2017.Study Design:Cross-sectional study.Methods:This study utilized da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Regardless, 207 of 222 (93%) positions were filled across the participating sports medicine fellowship programs, which was similar to previous years. 28 Bates et al 29 provided perspectives on the virtual interview process for radiation oncology residency programs and stated that virtual interviews led to increased efficiency by allowing residency programs to interview more applicants per day while allowing faculty to maintain their clinical duties. In addition, the reduced costs of the virtual interviews allowed applicants to attend more interviews and fellowship programs to interview more total applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, 207 of 222 (93%) positions were filled across the participating sports medicine fellowship programs, which was similar to previous years. 28 Bates et al 29 provided perspectives on the virtual interview process for radiation oncology residency programs and stated that virtual interviews led to increased efficiency by allowing residency programs to interview more applicants per day while allowing faculty to maintain their clinical duties. In addition, the reduced costs of the virtual interviews allowed applicants to attend more interviews and fellowship programs to interview more total applicants.…”
Section: Discussionmentioning
confidence: 99%
“…The study also indicated that 2013 was the only year in which there were more positions than applicants ( Figure 1 ). 16 Our study demonstrated that in 2013, in comparison to 2012, there was a decline from 32 to 9 sports medicine advertisements in JAAOS and from 12 to 9 in AJSM .…”
Section: Discussionmentioning
confidence: 57%
“…In 2018, Mulcahey et al 16 evaluated sports medicine fellowship match results from 2010–2017 to identify the overall match rate, number of programs filled, and number of applicants that were ranked by filled programs during this time period. The study utilized the American Orthopaedic Society for Sports Medicine match data including the number of applicants, number of matched/unmatched positions, and number of applicants matching into one of their top two positions.…”
Section: Discussionmentioning
confidence: 99%
“…Promising evidence has been published regarding fellowship match outcomes. 19 From 2010 to 2017, the mean number of programs participating in the fellowship match was 92.9 with an average of 244.8 applicants per year. 19 Of these programs, 75.8% matched all available fellowship positions and interviewed an average of 9.0 applicants per position compared to programs that did not fully match, which interviewed 6.5 applicants per position.…”
Section: Traditional Sports Medicine Fellowship Interview Processmentioning
confidence: 99%
“… 19 From 2010 to 2017, the mean number of programs participating in the fellowship match was 92.9 with an average of 244.8 applicants per year. 19 Of these programs, 75.8% matched all available fellowship positions and interviewed an average of 9.0 applicants per position compared to programs that did not fully match, which interviewed 6.5 applicants per position. Furthermore, Mulcahey and colleagues 19 revealed that 92.0% of these applicants successfully matched into a sports medicine fellowship program.…”
Section: Traditional Sports Medicine Fellowship Interview Processmentioning
confidence: 99%